Effects of the selection process on expatriates performance and adjustment to Turkey - Başçiftçi, Hülya (My University, 2000)
Bu araştırma Öğrenen Organizasyonlar Modelinin üç özel türk bankasında bulunup bulunmadığını, ve daha doğrusu öğrenme seviyelerin ve örgütsel sistemlerin arasındaki ilişkileri incelemek ve saptamak üzere gerçekleştirilmiştir. Üç farklı bankada çalışan 300 kişiden oluşan denek grubuna 53 soruluk bir anket uygulanmıştır. Anketlerden edilen sonuca göre, Ögrenen Organizasyonlar Modelinin üç özel türk bankasında bulunmaktadır. Dokuztane örgütsel sistemlerin üç örenme seviyelerini desteklediğini saptanmıştır çünkü aralarındaki ilişkiler gözlenmiştir. Bulgular iletişim, liderlik ve yönetim, performans yönetimi ve viziyon ve statejinin öğrenme üzerindeki en güçlü etkiyi göstermişlerdir. Bu araştırmadaki üç banka kıyaslanmıştır ve aralarındaki benzerlikler ve farklılıklar gözlenmiştir.

This study was designed to investigate if the Model of Learning Organizations is present in three private Turkish banks, and more specifically, if there is any relationship between levels of learning and organizational systems. A questionnaire composed of 53 questions was administrated to 300 subjects in three different banks. The data obtained from these questionnaires showed that the Model of Learning Organizations is present in the three banks. Besides, it was found that the nine systems support the three levels of learning since correlations among them were identified. The findings also indicated that communication, leadership and management, performance management and vision and strategy have the greatest effect on learning. The three banks in the research were compared and contrasted, so some similarities and differences among them were observed.
Keywords: İşgücü; İşgücü verimi